ACE vs. CBIT: which is better for investment and welfare? - Doina Maria Radulescu; Michael Stimmelmayr (Center for Economic Studies and ifo Institute (CESifo), 2006)
This paper analyses the switch to an ACE or to a CBIT type of tax system starting from the present German tax system. We show that in case an ACE type of reform is financed by an increase in the VAT and not in the profit tax, it might be preferred to a CBIT even in the context of an open economy. Moreover, the required exogenous increase in the profit tax rate cannot ensure revenue neutrality on its own due to the negative general equilibrium effects it triggers on the whole economy. For a CBIT, the exogenous reduction in the tax rates on corporate and non-corporate profits leads to better results than when we allow for an endogenous change in the VAT. The best results arise when the CBIT is accompanied by a provision for immediate write-off and a lower profit tax or when the ACE with no additional capital gains taxation on the household side is financed by an increase in the VAT.
Keywords: C68; D58; D92; E62; H25; 330; Kapitalertragsteuer; Wohlfahrtseffekt; CGE-Modelling; Theorie